ANALISIS DAYA SAING DAN KESIAPAN INDONESIA DALAM RANGKA INTEGRASI ASEAN : STUDI KASUS AUTOMOTIVES, RUBBER BASED, DAN AGRO BASED PRODUCTS - Adrian D. Lubis (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2011)
In AseAN economic community-Aec by 2015, Indonesia is predicted still left behind in competitiveness from other AseAN countries, particularly singapore, malaysia and thailand. Based on the AseAN trade data base, Indonesia has only 2 sector industry which have competitiveness from the 12 priority sector in Aec’s blue print. this paper aims, firstly, to analyse the impact of integration among AseAN countries on the performance of industrial linkages automotives, rubber based, agro based products in Indonesia. secondly, to determine the impact of liberalization among AseAN countries on a map of the competitiveness of automotives industry, rubber based, agro based products in Indonesia, thirdly, to know how the readiness the trade facilitation in sectors priority of automotives, rubber based and agro based products, and finally to determine the policy formulation of the priority sector in the preparation of the implementation of the Aec. the result suggest that almost of 3 industries, Indonesia is with low level IIt and competitiveness (RcAB). moreover, Indonesia still attracts FdI in order to increase the performance of IIt dan RcAB.